(untitled) (Eurasian Scientific Herald, 2023)
The article deals with the problems of using interactive methods and their role in the formation of critical thinking in schoolchildren as a means of personal self-development. Also, the introduction of technology for the development of students’ critical thinking in the classroom was discussed as well in the article